Development of an electronic nose to characterize geosmin and 2-methylisoborneol of water collected from different phases in water treatment plants - Bingyang Wang; Yu Yan; Xiaodan Li; Hongwei Zhai; Xia Han; Gang Lu; Zhiyong Chang (Water Research, 2026)

Multi-endpoint in vitro toxicity profiling of heated tobacco products versus e-cigarettes under air-liquid interface exposure - Hongjuan Wang; Yushan Tian; Shigang Li; Peizhen Li; Ningning Geng; Xiao Li; Lili Cui; Yaning Fu; Shulei Han; Huan Chen; Hongwei Hou (Toxicology in Vitro, 2026)

Stromatolite-rich red tidal-flat dolostones in the Shennongjia Group: Origins and late Mesoproterozoic biogeochemical cycling - Shourui Dai; Hongwei Kuang; Zuozhen Han; Yongqing Liu; Nan Peng; Changfu Fan; Yuchong Wang; Zhaohong Chen; Chao Han; Chenlin Zhu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

High performance of self-regulating temperature solid amine hollow fibers for direct air capture of CO2 - Jianxin Zhang; Liu Yang; Hongwei Yang; Zhenhuan Li; Shanghan Han; Xiaoyao Tan (Journal of Environmental Chemical Engineering, 2026)

A green ferrofluid based on hydrated deep eutectic solvent for dispersive liquid-liquid microextraction of bisphenols from edible oil - Jiangping Cao; Zetong Wang; Chongchong Du; Xueli Zhuang; Jimei Zhou; Juanjuan Wei; Hongwei Di; Yangying Han (Food Chemistry, 2026)

Unlocking the decadal history of algal blooms in shallow lakes: A spectral polarity framework reveals nonlinear temperature responses - Han Zhang; Jinhui Jeanne Huang; Hongwei Guo (Water Research, 2026)

Nanoconfinement-enhanced cerium@carbon nanotubes composites for adsorption of fluoride - Erming Ouyang; Guangzhe Han; Yi Zhang; Wei Song; Hongwei Yang; Rui Zhao (Environmental Research, 2026)

How alternate wetting and drying irrigation drives carbon reduction in rice-crab cocultural ecosystem: A quantitative assessment - Hongwei Han; Yikui Bai; Feng Zhang; Haixia Liu; Yijian Tong; Daocai Chi; Taotao Chen (Agriculture, Ecosystems & Environment, 2026)

Identification and expression profiling of SPL family genes in industrial hemp under NaHCO3 stress - Kun Cao; Xuehai Li; Jing Bian; Pan Wang; Hao Zhu; Pengfei Chu; Xiaoyan Zhang; Peiyu Chu; Hongwei Zhang; Tianliang Wang; Xu Han; Xiaonan Wang (Plant Gene, 2026)

A microfluidic human blood–brain barrier model reveals neurovascular toxicity and barrier disruption induced by E-cigarette additives - Changfeng Yin; Xiao Li; Feiju Yu; Xuran Wang; Yushan Tian; Hongjuan Wang; Yibo Chen; Shulei Han; Huan Chen; Hongwei Hou (Chemico-Biological Interactions, 2026)

Periodic formation configuration design in multi-body systems based on semi-analytical gradient information - Qian Li; Zhenyu Li; Hongwei Han; Dong Qiao (Advances in Space Research, 2026)

From biomarkers to the risk index: a novel integrated model using multidimensional urinary biomarkers to quantify e-cigarette exposure - Lili Cui; Shulei Han; Pengpeng Yu; Ruijuan Miao; Xingfang Cun; Yuan Zhang; Peipei Ren; Pengxia Feng; Lingxiao Song; Yaning Fu; Hongjuan Wang; Yushan Tian; et al. (Archives of Toxicology, 2026)

A Functional Limosilactobacillus reuteri ZY18 Strain: Probiotic Properties and Associated Anti-inflammatory Responses Against ETEC K88 Infection - Xin Xu; Jiahao Meng; Hongwei Zhang; Kun Meng; Zihan Zhang; Jiayi Sheng; Hongying Cai; Weiwei Liu; Yunsheng Han; Peilong Yang (Probiotics and Antimicrobial Proteins, 2026)

Rice-crab co-culture mitigates reactive gaseous N losses and increases economic benefits - Feng Zhang; Guimin Xia; Yuanze Qiu; Hongwei Han; Haixia Liu; Benji Yi; Bohao Li; Daocai Chi; Taotao Chen (Field Crops Research, 2026)

Divergent mechanisms of menthol and tobacco e-cigarette toxicity in a 3D airway organoid model: Metabolic disruption and immunosuppression versus Th2-Allergic inflammation and apoptotic stress - Xiao Li; Yushan Tian; Hongjuan Wang; Yuanyuan Jiang; Yibo Chen; Shulei Han; Zheng Song; Lili Cui; Huan Chen; Hongwei Hou (Chemico-Biological Interactions, 2026)

Context-dependent links between microbial co-occurrence topology and nitrogen mineralization in two adjacent subalpine Picea asperata stands - Lixia Wang; Haoying Gao; Shuangjia Fu; Lin Xu; Li Zhang; Han Li; Chengming You; Sining Liu; Hongwei Xu; Jiao Li; Bo Tan; Zhenfeng Xu (Plant and Soil, 2026)

Effects of red clover extract on growth performance, nutrient digestibility, antioxidant status, and rumen microbiota in fattening Hu sheep - Hengbo Ye; Lu Li; Hongwei Duan; Han Zhang; Mengshu Zhou; Shengguo Zhao; Yuyang Yin; Junshi Shen; Shengyong Mao; Weiyun Zhu (Animal Feed Science and Technology, 2026)

Contrasting Effects of Nitrogen Input on Soil Carbon Pools in Arid and Humid Climates - Shibing Jia; Cuihuan Li; Zhenfeng Xu; Bo Tan; Xinglei Cui; Guopeng Liang; Han Li; Li Zhang; Lin Xu; Hongwei Xu; Sining Liu; Lixia Wang; et al. (Global Change Biology, 2026)
Nitrogen (N) input affects soil organic carbon (SOC) dynamics and storage by specifically influencing the light (LFOC) and heavy fractions of organic C (HFOC). While the effects of N input on SOC pools are known, its specific influence in arid and humid regions remains unresolved, although it is critically important to predict carbon–climate feedback and SOC accumulation. We conducted a meta‐analysis of 881 paired observations from 60 studies to quantify the climate‐specific responses of SOC, LFOC, and HFOC contents to N input, thereby revealing distinct effects in arid versus humid regions. N input increased the LFOC content by 25% in arid regions, whereas the HFOC and SOC contents remained unchanged. This LFOC accumulation may reflect increased plant C inputs, suppressed microbial decomposition, and strong physical protection compared with soil without N input. Conversely, in humid regions, N input increased the HFOC and SOC contents by 10%. These increases were associated with the following four mechanisms: (1) increases in plant and microbial necromass production after N input, (2) microbially‐mediated formation of the HFOC from the LFOC, (3) accelerated lignin‐derived C accumulation due to suppressed saprotrophic fungal decomposition, and (4) raised physico–chemical stabilization by various biotic and abiotic mechanisms. Specifically, increases in LFOC content in arid regions occurred under medium to high N input rates (≥ 50 kg N ha −1 year −1 ), whereas increases in HFOC and SOC contents in humid regions occurred only under medium N input (50–100 kg N ha‐1 year −1 ). These increases occurred primarily after periods of N input longer than 5 years and mainly in topsoil (

MOF-derived Cu/Co-doped nanocarbons for selective nitrate to ammonia electrocatalysis: Synergistic adsorption-hydrogenation mechanism - Yuanbo Zhou; Hongwei Zhu; Siru Chen; Weiqing Han; Siqi Tong; Yi Wang (Fuel, 2026)

Engineering Li+ solvation sheath and continuous transport pathways via weak-field ligand diluent for subzero lithium-ion batteries - Hao Huang; Jingang Zheng; Yiyang Zhao; Weichen Han; Hongyang Li; Lixiang Li; Hongwei Zhao; Han zhang; Baigang An; Chengguo Sun (Chemical Engineering Journal, 2026)

Response of soil humic substances to snowpack decline across different soil layers in the subalpine forest - Li Zhang; Wenlan Huang; Yao Liu; Sining Liu; Han Li; Bo Tan; Chengming You; Hongwei Xu; Lin Xu; Zhenfeng Xu; Yalin Yuan; Jiao Li; et al. (CATENA, 2026)

Stand age drives divergent microbial metabolic limitations and ecosystem multifunctionality between rhizosphere and bulk soils in subtropical Cryptomeria japonica plantations - Shanshan Huang; Yi Jian; Jing Li; Dengjie Zhou; Zhenfeng Xu; Bo Tan; Xinglei Cui; Tong Zhang; Lin Xu; Han Li; Li Zhang; Lixia Wang; et al. (Soil Ecology Letters, 2026)

Urban expansion and climate variability drive hypoxia: A Landsat-based 1986–2024 dissolved oxygen climatology in China’s Greater Bay area - Xiaotong Zhu; Hongwei Guo; Han Zhang; Peng Zhang; Shiqiang Zhou; Minghua Zhou (Journal of Hydrology, 2026)

The silent saboteurs: How ultraviolet (UV)-aged polystyrene nanoplastics disrupt the regenerative capacity of goldfish (Carassius auratus) caudal fins - Deshan Chen; Tian Wang; Lei Han; Hongwei Wang; Mohammad Mehdi Ommati; Ping Sun (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Multifunctional microbial desalination cell for industrial wastewater treatment: Synergistic pyridine degradation, nitrogen removal and desalination - Ying Guan; Run Liu; Yuanbo Zhou; Hongwei Zhu; Siqi Tong; Yi Wang; Kajia Wei; Weiqing Han (Journal of Environmental Chemical Engineering, 2026)

The formation mechanism of ultra-deep gas condensate reservoirs: A case study of the Shunbei No. 4 strike-slip fault zone in the Tarim Basin, NW China - Xin Yang; Hongwei Ping; Zicheng Cao; Lu Yun; Haiying Li; Jun Han; Feng Geng; Cheng Huang; Xinle Zhang; Zhongdeng Lu; Honghan Chen (Journal of Asian Earth Sciences, 2026)

Enhancing physicochemical and antibacterial properties of pectin-based films via PA-Zn nanoparticle doping for antimicrobial food packaging application - Han Wang; Weiqiang Pan; Hongwei He; Xiaochen Cheng; Xiaoyu Chen; Chengzhen Liu (Journal of Stored Products Research, 2026)

Unlocking potassium sustainability: Rice-crab co-culture system enhances potassium balance - Haixia Liu; Xuran Liu; Feng Zhang; Hongwei Han; Yinghao Li; XiaoLi Wu; Guangyan Liu; Daocai Chi; Jun Meng; Taotao Chen (Field Crops Research, 2026)

Patterns and drivers of plant- and microbial-derived carbon in a cedar plantation chronosequence of subtropical China - Yuehan Wang; Yu Li; Chengming You; Hongwei Xu; Han Li; Lin Xu; Li Zhang; Lixia Wang; Sining Liu; Bo Tan; Yaling Yuan; Jiao Li; et al. (Plant and Soil, 2026)

South China in the Rodinia-Gondwana transition: Constrains from the Ediacaran Doushantuo Formation of the north Yangtze Block - Lisha Hu; Jie Yang; Yuansheng Du; Zuozhen Han; Hongwei Kuang; Yongqing Liu; Chao Han; Yi Zhang; Wei Jin; Le Wan (Precambrian Research, 2026)

Intelligent and interpretable forecasting method for ice-jam flood disaster levels based on fusion model - Yu Li; Hongwei Han; Fuchang Tian; Ximin Yuan; Dongxu Yang (Journal of Hydrology, 2026)

Performance study of microbial fuel cell stack system for treating fine chemical wastewater - Hongwei Chen; Ao Lei; Yangfan Song; Yanmin Li; Qianyun Wu; Liuping He; Chao Han; Pei Wu; Xin Yang (Bioresource Technology, 2026)

Ectomycorrhizal exploration types shape soil enzyme activity, decomposition, and nitrogen dynamics in subalpine forests - Lixia Wang; Haoying Gao; Shuangjia Fu; Huichao Li; Lin Xu; Li Zhang; Han Li; Chengming You; Sining Liu; Hongwei Xu; Jiao Li; Bo Tan; et al. (Plant and Soil, 2026)

Photobiomodulation Reduces Fibrous Scar Formation After Spinal Cord Injury by Downregulating CXCL3 Expression in Macrophages - Zhihao Zhang; Hongwen Gu; Ting He; Yuanhang Zhao; Shilei Tang; Kangen Han; Yin Hu; Hongwei Wang; Hailong Yu (Molecular Neurobiology, 2026)

Changes in litter chemical properties mediate the effects of soil arthropods on the microbial community during litter decomposition in a subalpine forest - Aomiao Wu; Jingru Liu; Rui Yin; Lin Xu; Chengming You; Zhenfeng Xu; Li Zhang; Han Li; Lixia Wang; Sining Liu; Hongwei Xu; Bo Tan (Applied Soil Ecology, 2026)

Rice-crab coculture produces higher carbon sink and eco-economic benefits - Hongwei Han; Taotao Chen; Feng Zhang; Haixia Liu; Yikui Bai; Daocai Chi (Field Crops Research, 2025)

Strategic A-site composition design in Mn-based perovskites for enhancing toluene oxidation: Activation mechanism and promotion effect of lattice oxygens - Hongwei Jian; Yu Wu; Qiuyan Zhang; Aijie Wang; Haojie Yang; Huaiyu Zhang; Chong Han (Chemical Engineering Journal, 2025)

Strip clearcutting and replanting effects on soil organic carbon, microbial necromass carbon, and microbial carbon use efficiency in Chinese fir plantations - Xinran Zhao; Huiling Zhou; Hongwei Xu; Lin Xu; Chengming You; Li Zhang; Bo Tan; Zhenfeng Xu; Han Li; Lixia Wang; Sining Liu; Xinglei Cui; et al. (Plant and Soil, 2025)

PPAR γ changing ALDH1A3 content to regulate lipid metabolism and inhibit lung cancer cell growth - Xinyuan Tian; Xiaoping Bai; Yunqi Han; Yu Ye; Meiling Peng; Hongwei Cui; Kai Li (Molecular Genetics and Genomics, 2025)

Quantitative Evaluation of Gas Injection Contribution Using Fluid Inclusion Data: A Case Study of the Condensate Gas Reservoirs of the Eastern Shunbei Area in the Tarim Basin - Zicheng Cao; Lu Yun; Hongwei Ping; Haiying Li; Feng Geng; Jun Han; Cheng Huang; Xin Yang; Honghan Chen (Journal of Earth Science, 2025)

Controllable synthesis of low-crystallinity Ni6MnO8 with abundant oxygen vacancies for effective ozone decomposition - Aijie Wang; Yu Wu; Qiuyan Zhang; Hongwei Jian; Chong Han (Journal of Environmental Sciences, 2025)

High energy electron irradiation promotes the space weathering process on the nearside of the Moon - Zhenyu Xu; Yazhou Yang; Longlong Zhang; Shuai Li; Hongwei Li; Panpan Zhang; Mengyuan Zhang; Haolin Yin; Mengze Tao; Zichen Wei; Hao Zhang; Lianghai Xie; et al. (Earth and Planetary Science Letters, 2025)

Multiphysics coupled modelling of a tube-plate-type packed-bed reactor for CaO/Ca(OH)2 thermochemical energy storage operated in ‘electricity-in-steam-out’ mode - Binquan Wang; Liuzhen Han; Hongwei Shen; Yang Qiao; Jie Sun (Chemical Engineering Journal, 2025)

Antimony-doped tin oxide/graphite composite counter electrode for hole transport layer-free printable mesoscopic perovskite solar cells with enhanced hole collection - Qiaojiao Gao; Kai Chen; Xiaoyu Li; Jiale Liu; Qian Yue; Yuan Shi; Junwei Xiang; Chuang Yang; Song Shen; Shichao Zhang; Siqi Jiang; Shijie Guan; et al. (Chemical Engineering Journal, 2025)

Quantifying the impact of thermal maturity on carbon isotope variations of marine oils from the Shunbei ultra-deep petroleum system, Tarim Basin - Zhongdeng Lu; Hongwei Ping; Zicheng Cao; Lu Yun; Haiying Li; Feng Geng; Jun Han; Cheng Huang; Honghan Chen (Organic Geochemistry, 2025)

Contrasting effects of different acid rain types on soil nitrogen pools - Xingyu Pan; Yi Jian; Zhenfeng Xu; Bo Tan; Xinglei Cui; Tong Zhang; Lin Xu; Han Li; Li Zhang; Hongwei Xu; Sining Liu; Lixia Wang; et al. (Journal of Environmental Management, 2025)

Water-activated Cu3FeO bimetallic composites outperform Cu3MnO and CuO in ozone removal under high humidity - Aijie Wang; Xuehui Shen; Yu Wu; Qiuyan Zhang; Hongwei Jian; Chong Han (Journal of Environmental Chemical Engineering, 2025)

Succession of biological soil crusts modifies patterns of soil eukaryotic communities along a precipitation gradient - Lin Xu; Yongping Kou; Xiangzhen Li; Chaonan Li; Jiabao Li; Bingchang Zhang; Lixia Wang; Hongwei Xu; Chengmin You; Han Li; Sining Liu; Yang Liu; et al. (Applied Soil Ecology, 2025)

Exploring the role of the rhizosphere in soil carbon cycling: impacts on pools and components of SOC along a chronosequence of Cryptomeria japonica plantations in subtropical China - Dengjie Zhou; Yaling Yuan; Jing Li; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Lin Xu; Li Zhang; Hongwei Xu; Lixia Wang; Sining Liu; et al. (Plant and Soil, 2025)

Seasonal dynamics of ammonia-oxidizing archaea and bacteria in subalpine forests of western Sichuan - Li Zhang; Su Chen; Zebin Jiao; Sining Liu; Wenlan Huang; Lulu Huang; Liyun Yu; Lixia Wang; Bo Tan; Hongwei Xu; Lin Xu; Chengming You; et al. (Plant and Soil, 2025)

Rapid identification of time-varying aerodynamic parameters for aeroassisted vehicle via asynchronous iterative filtering - Qian Pan; Hongwei Han; Dong Qiao (Advances in Space Research, 2025)

In vitro toxicological assessment using NCI-H292 cells of the relationship between cytotoxic effects and chemical composition in flavored e-liquids - Shuhong Zhang; Yumeng Zhang; Hongjuan Wang; Shulei Han; Huan Chen; Hongwei Hou (Archives of Toxicology, 2025)

Alkyl chain length engineering of zwitterionic sulfobetaine passivators for efficient printable mesoscopic perovskite solar cells - Xufeng Xiao; Kai Chen; Mi Qin; Xiaoyu Li; Ranjun Meng; Xiaoru Wang; Yang Zhou; Anyi Mei; Hongwei Han (Chemical Engineering Journal, 2025)

Introgression of quantitative trait locus qSFWI6D from Aegilops tauschii improves salt tolerance in wheat at seedling stage - Jinhao Han; Hongyu Ren; Mengjia Sun; Mingxuan Li; Cunyao Bo; Jiachuang Fang; Hongwei Wang; Yunlong Pang; Xiaoqian Wang (Theoretical and Applied Genetics, 2025)

Forest conversion and root trenching reshape microbial functions regulating root litter decomposition and soil carbon dynamics - Lixia Wang; Shuangjia Fu; Haoying Gao; Huichao Li; Yang Liu; Lin Xu; Li Zhang; Han Li; Chengming You; Sining Liu; Hongwei Xu; Bo Tan; et al. (Applied Soil Ecology, 2025)

Impact of Methane Emissions on Future Stratospheric Ozone Recovery - Na Liu; Fei Xie; Yan Xia; Yingli Niu; Hongwei Liu; Xinyuan Xiang; Yuanyuan Han (Advances in Atmospheric Sciences, 2025)

Nintedanib abrogates patient vitreous-induced Akt activation and tube formation of human retinal microvascular endothelial cells - Qiang Li; Xiaoping Zhou; Yanhui Yang; Qing Zhang; Zhiyuan Li; Haote Han; Fang Yuan; Hongwei Deng; Hetian Lei; Yajian Duan (Tissue and Cell, 2025)

Enhancing the thermal stability of activated carbon in VOCs adsorption by incorporation of silicon-doped CQDs - Hongwei Ren; Liang Han; Qing Li; Xiaoyun Liu; Xiaoyu Huang; Luyu Jia; Zhaoxiong Huang; Jinfeng Zhang (Journal of Environmental Chemical Engineering, 2025)

Hydrogen-substituted graphdiyne-facilitated polyamide membrane with improvement of water permeance - Wenjing Han; Yawen Tian; Zhou Qu; Chenyu Lai; Haoran Wang; Qianxi Yang; Hongwei Fan; Hong Meng (Desalination, 2025)

The heterogeneous response in leaf traits among seasons and plant types of an evergreen broadleaf forest in western China to nitrogen addition was regulated by fertilization intensity - Wenzheng Chang; Qiu Song; Tianxing Liang; Jie Chen; Lixia Wang; Han Li; Li Zhang; Chengming You; Hongwei Xu; Lin Xu; Bo Tan; Zhenfeng Xu; et al. (Plant and Soil, 2025)

Soil nutrients determine multidimensional absorptive root traits of Cryptomeria japonica var. sinensis plantations along a chronosequence in subtropical forest - Chunran Liu; Lihua Wang; Jing Li; Petr Heděnec; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Lin Xu; Hongwei Xu; Li Zhang; Lixia Wang; et al. (Journal of Environmental Management, 2025)

Nitrogen addition and plant functional type mediate the mesofauna-driven litter element release of subtropical forest - Jihong Li; Qun Liu; Rui Yin; Chengming You; Li Zhang; Han Li; Lixia Wang; Hongwei Xu; Lin Xu; Sining Liu; Bo Tan; Zhenfeng Xu (Plant and Soil, 2025)

An optimal strategy for estimating chlorophyll-a concentration in case II waters to support sustainable development goals - Shang Tian; Xiaotong Zhu; Han Zhang; Hongwei Guo; Zijie Zhang; Jinhui Jeanne Huang (Advances in Space Research, 2025)

Recurrence of Cerebral Arteriovenous Malformation Following Complete Obliteration Through Endovascular Embolization - Qiang Hao; Haibin Zhang; Heze Han; Hengwei Jin; Li Ma; Ruinan Li; Zhipeng Li; Anqi Li; Kexin Yuan; Qinghui Zhu; Ke Wang; Runting Li; et al. (Translational Stroke Research, 2025)

Exosomal miR-27a-5p attenuates inflammation through Toll-like receptor 7 in foodborne Salmonella infections - Mingjuan Qu; Shengfa Su; Linlin Jiang; Xin Yu; Jianlong Zhang; Hongwei Zhu; Kexue Han; Xingxiao Zhang (Veterinary Microbiology, 2025)

Climate outweighs fertiliser effects on soil phoD-harbouring communities in agroecosystems - Lin Xu; Yongping Kou; Qian Mao; Xiangzhen Li; Chaonan Li; Bo Tu; Jiabao Li; Lihua Tu; Lixia Wang; Hongwei Xu; Chengming You; Han Li; et al. (Soil Biology and Biochemistry, 2025)

Surgical treatment of Meniere’s disease - Yixu Wang; Hongwei Zheng; Xin Ma; Lin Han; Tongxiang Diao; Lisheng Yu; Maoli Duan (Science Bulletin, 2025)

Engineering oxygen vacancies in acid-etched MgMn2O4 for efficiently catalytic benzene combustion: Synergistic activation of gaseous oxygen and surface lattice oxygen - Yu Wu; Dongjing Lei; Aijie Wang; Qiuyan Zhang; Hongwei Jian; Haojie Yang; Chong Han (Journal of Hazardous Materials, 2025)

Soil phosphorus dynamics and its correlation with ectomycorrhizal fungi following forest conversion in subtropical conifer (Picea asperata) forests - Lixia Wang; Shiyu Song; Huichao Li; Yang Liu; Lin Xu; Han Li; Chengming You; Sining Liu; Hongwei Xu; Bo Tan; Zhenfeng Xu; Li Zhang; et al. (European Journal of Soil Biology, 2025)

Fabrication of Curdlan connected honeycomb-like 3D BN-CNT network for enhancing the thermal conductivity of epoxy composites - Chen Han; Jie Ma; Hongwei He; Wenwen Yu; Yuchen Zhang; Chen Cui; Qingyuan Ma; Yushi Jin (Chemical Engineering Journal, 2025)

Dynamics of soil phosphorus fractions during the early recovery stage of two typical plantations in China after strip clearcutting - Linhui Zhang; Jihong Li; Su Chen; Wenlan Huang; Lulu Huang; Hongfeng Zhu; Yuanxiang Tang; Han Li; Chengming You; Lixia Wang; Sining Liu; Hongwei Xu; et al. (CATENA, 2025)

Forest thinning effects on soil carbon stocks and dynamics: Perspective of soil organic carbon sequestration rates - Qing Qu; Hongwei Xu; Lin Xu; Chengming You; Bo Tan; Han Li; Li Zhang; Lixia Wang; Sining Liu; Zhenfeng Xu; Sha Xue; Minggang Wang (CATENA, 2025)

Fertilization effects on soil organic matter chemistry - Dengjie Zhou; Rui Mou; Lihua Wang; Jingru Liu; Yuanxiang Tang; Ji Chen; Petr Heděnec; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Li Zhang; et al. (Soil and Tillage Research, 2025)

Resource utilization strategy based on the deactivation mechanism of V2O5-WO3/TiO2 catalyst - Cheng Dong; Junxuan Yao; Jianqiang Shi; Lina Han; Hongwei Qin; Zhihua Zhang; Qinghai Zhang; Jiancheng Wang (Fuel, 2025)

Zeolite mitigates alternate wetting and drying – Induced potassium depletion and enhances potassium balance in rice paddies: A 6-year field study - Hongwei Han; Taotao Chen; Yongchao Su; Shu Zhang; Qing Zhao; Yidi Sun; Yikui Bai; Daocai Chi (Field Crops Research, 2025)

Hepatotoxic effects of environmentally relevant concentrations of polystyrene microplastics on senescent Zebrafish (Danio rerio): Patterns of stress response and metabolomic alterations - Pengfei Xie; Mohammad Mehdi Ommati; Deshan Chen; Weijun Chen; Lei Han; Xinquan Zhao; Hongwei Wang; Shixiao Xu; Ping Sun (Aquatic Toxicology, 2025)

Multi-omics analysis of the effects of low-temperature storage on chilling injury of bitter gourd - Hongwei Wang; Ling Li; Da-Wen Sun; Lili Ma; Lichun Han; Xuelian He; Qing Wang; Christopher B. Watkins; Jinhua Zuo; Yanyan Zheng (Postharvest Biology and Technology, 2024)

Construction of electron-deficient Co on the nanoarrays enhances absorption and direct electron transfer to accelerate electrochemical nitrate reduction - Zhifeng Gao; Xueying Duan; Xu Yin; Wei Li; Hongwei Zhu; Kajia Wei; Weiqing Han (Journal of Hazardous Materials, 2024)

Impact of dual Bt-transgenic maize (2A7) on soil microbial communities and enzyme activities: A comparative study with control variety Z58 - Aliya Fazal; Minkai Yang; Hongwei Han; Guihua Lu; Chenyu Hao; Xiaohui Lai; Yuhang Song; Hanke Ma; Tongming Yin; Jinliang Qi; Shucun Sun; Kechang Niu; et al. (Environmental Research, 2024)

Efficient electrocatalytic bromine evolution and extraction from wastewater by oxygen vacancy enriched Ti/Ov-Co3O4-NRs electrode - Xu Yin; Renping Li; Wei Li; Zhifeng Gao; Kajia Wei; Hongwei Zhu; Liankai Gu; Yun Jiang; Weiqing Han (Desalination, 2024)

Prescribed modal vibration control and disturbance load analysis of rigid-flexible satellites - Zeqiang Han; Hongwei Xia; Guan Wang; Guangcheng Ma (Advances in Space Research, 2024)

Divergent responses of woody plant leaf and root non-structural carbohydrates to nitrogen addition in China: Seasonal variations and ecological implications - Rui Mou; Yi Jian; Dengjie Zhou; Jihong Li; Yao Yan; Bo Tan; Zhenfeng Xu; Xinglei Cui; Han Li; Li Zhang; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2024)

A novel Tree-augmented Bayesian network for predicting rock weathering degree using incomplete dataset - Chen Wu; Hongwei Huang; Jiayao Chen; Mingliang Zhou; Shiju Han (International Journal of Rock Mechanics and Mining Sciences, 2024)

Enhanced flame retardancy and mechanical properties of poly (lactic acid) composites via piperazine pyrophosphate and nanoscale cerium dioxide synergistic flame retarding and uniaxial pre-stretching - Tianyi Ma; Lijing Han; Gaofei Zheng; Junjia Bian; Yan Zhao; Hongwei Pan; Huiliang Zhang (Chemical Engineering Journal, 2024)

Changes in soil microbial community and function across stand age of Cryptomeria japonica var. sinensis plantations in subtropical China - Li Zhang; Shichen Xiong; Ya Shen; Chengming You; Han Li; Lixia Wang; Sining Liu; Bo Tan; Hongwei Xu; Lin Xu; Jiao Li; Zhenfeng Xu (Applied Soil Ecology, 2024)

Tree species-mediated soil properties shape soil fauna community structure more strongly in the soil layer: Evidence from a common garden experiment - Jingru Liu; Aomiao Wu; Rui Yin; Zhenfeng Xu; Chengming You; Li Zhang; Lin Xu; Hongwei Xu; Lixia Wang; Han Li; Sining Liu; Yang Liu; et al. (Applied Soil Ecology, 2024)

CORO1C Regulates the Malignant Biological Behavior of Ovarian Cancer Cells and Modulates the mRNA Expression Profile through the PI3K/AKT Signaling Pathway - Na Lu; Yongfeng Guo; Lixin Ren; Hongwei Zhao; Lijun Yan; Haiqiong Han; Sanyuan Zhang (Cell Biochemistry and Biophysics, 2024)

Multiomics comprehensive analysis of pre-storage low-temperature on cowpea metabolism - Lichun Han; Zhengrong Wang; Qing Wang; Da-Wen Sun; Xuelian He; Hongwei Wang; Lili Ma; Chunmei Bai; Christopher B. Watkins; Jinhua Zuo; Yanyan Zheng (Postharvest Biology and Technology, 2024)

Experimental study on the hydrodynamic of foldable-wing unmanned aerial-underwater vehicles during water-exit process - Zhaoliang Han; Jian Cao; Ye Li; Hongwei Li; Zipeng Du; Jinyu Fu; Lei Wan (Ocean Engineering, 2024)

Design and analysis of grid mooring system for gravity net cage with a comprehensive optimization method - Gang Ma; Zhongxu Du; Hongwei Wang; Huawei Han; Yuhai Sun; Hailong Chen; Zilin Jiang (Ocean Engineering, 2024)

Efficient ozone decomposition by amorphous Mn–Ni bimetallic catalysts under an entire humidity environment - Aijie Wang; Yu Wu; Xuehui Shen; Qiuyan Zhang; Hongwei Jian; Chong Han (Journal of Environmental Chemical Engineering, 2024)

Central role of Sigma-1 receptor in ochratoxin A-induced ferroptosis - Wenying Chen; Lingyun Han; Ruiran Yang; Hongwei Wang; Song Yao; Huiqiong Deng; Shuangchao Liu; Yao Zhou; Xiao Li Shen (Archives of Toxicology, 2024)

Convergent Neuroimaging and Molecular Signatures in Mild Cognitive Impairment and Alzheimer’s Disease: A Data-Driven Meta-Analysis with N = 3,118 - Xiaopeng Kang; Dawei Wang; Jiaji Lin; Hongxiang Yao; Kun Zhao; Chengyuan Song; Pindong Chen; Yida Qu; Hongwei Yang; Zengqiang Zhang; Bo Zhou; Tong Han; et al. (Neuroscience Bulletin, 2024)
The current study aimed to evaluate the susceptibility to regional brain atrophy and its biological mechanism in Alzheimer’s disease (AD). We conducted data-driven meta-analyses to combine 3,118 structural magnetic resonance images from three datasets to obtain robust atrophy patterns. Then we introduced a set of radiogenomic analyses to investigate the biological basis of the atrophy patterns in AD. Our results showed that the hippocampus and amygdala exhibit the most severe atrophy, followed by the temporal, frontal, and occipital lobes in mild cognitive impairment (MCI) and AD. The extent of atrophy in MCI was less severe than that in AD. A series of biological processes related to the glutamate signaling pathway, cellular stress response, and synapse structure and function were investigated through gene set enrichment analysis. Our study contributes to understanding the manifestations of atrophy and a deeper understanding of the pathophysiological processes that contribute to atrophy, providing new insight for further clinical research on AD.

High‑oxygen-modified atmospheric packaging delays flavor and quality deterioration in fresh-cut broccoli - Xuelian He; Lihong Wang; Jiejie Tao; Lichun Han; Hongwei Wang; Xiaoyan Zhao; Jinhua Zuo; Yanyan Zheng (Food Chemistry, 2024)

Ammonia detection based on Pd/Rh-GaN and recognition of disease markers of nitrogen compounds assistant by deep learning - Jiexu Shi; Dan Han; Yuxuan Wang; Qi Duan; Hongwei Li; Xiaqin Zhang; Hua Liang; Shengbo Sang (Chemical Engineering Journal, 2024)

Consistent community assembly but contingent species pool effects drive β‐diversity patterns of multiple microbial groups in desert biocrust systems - Lin Xu; Xiangzhen Li; Xin Tang; Yongping Kou; Chaonan Li; Jiabao Li; Minjie Yao; Bingchang Zhang; Lixia Wang; Hongwei Xu; Chengming You; Han Li; et al. (Molecular Ecology, 2024)
One of the key goals of ecology is to understand how communities are assembled. The species co‐existence theory suggests that community β‐diversity is influenced by species pool and community assembly processes, such as environmental filtering, dispersal events, ecological drift and biotic interactions. However, it remains unclear whether there are similar β‐diversity patterns among different soil microbial groups and whether all these mechanisms play significant roles in mediating β‐diversity patterns. By conducting a broad survey across Chinese deserts, we aimed to address these questions by investing biological soil crusts (biocrusts). Through amplicon‐sequencing, we acquired β‐diversity data for multiple microbial groups, that is, soil total bacteria, diazotrophs, phoD ‐harbouring taxa, and fungi. Our results have shown varying distance decay rates of β‐diversity across microbial groups, with soil total bacteria showing a weaker distance‐decay relationship than other groups. The impact of the species pool on community β‐diversity varied across microbial groups, with soil total bacteria and diazotrophs being significantly influenced. While the contributions of specific assembly processes to community β‐diversity patterns varied among different microbial groups, significant effects of local community assembly processes on β‐diversity patterns were consistently observed across all groups. Homogenous selection and dispersal limitation emerged as crucial processes for all groups. Precipitation and soil C:P were the key factors mediating β‐diversity for all groups. This study has substantially advanced our understanding of how the communities of multiple microbial groups are structured in desert biocrust systems.

Differences in the response of normal oral mucosa, oral leukoplakia, oral squamous cell carcinoma-derived mesenchymal stem cells, and epithelial cells to photodynamic therapy - Qianyun Guo; Xiaoli Ji; Lei Zhang; Xingyun Liu; Yutian Wang; Zijian Liu; Jianqiu Jin; Ying Han; Hongwei Liu (Journal of Photochemistry and Photobiology B: Biology, 2024)

Machine learning elucidates ubiquity of enhanced ozone air pollution in China linked to the spring festival effect - Baizhen Zhu; Jie Fang; Yunjiang Zhang; Jian Qiu; Kehong Chen; Kexin Zhang; Hongwei Liang; Han Yang; Yihua Ding; Xinlei Ge (Atmospheric Pollution Research, 2024)

In vivo transgenic studies confirm the critical acylation function of LeBAHD56 for shikonin in Lithospermum erythrorhizon - Liu Yang; Changyi Wang; Xiaohui Lai; Suo Jin; Xuan Wang; Zhongling Wen; Minkai Yang; Aliya Fazal; Yuhang Ding; Zhongyi Li; Jinfeng Cai; Guihua Lu; et al. (Plant Cell Reports, 2024)

Decreased snow depth inhibits litter decomposition via changes in litter microbial biomass and enzyme activity - Ting Du; Li Zhang; Yulian Chen; Yu Zhang; Hemeng Zhu; Zhenfeng Xu; Bo Tan; Chengming You; Yang Liu; Lixia Wang; Sining Liu; Hongwei Xu; et al. (Science of The Total Environment, 2024)

High-Performance low-k Poly(dicyclopentadiene)-POSS nanocomposites achieved by frontal polymerization - Dai-Lin Zhou; Jian Wang; Hongwei Bai; Di Han; Qiang Fu (Chemical Engineering Journal, 2024)

Effects of forest thinning on soil microbial biomass and enzyme activity - Hongwei Xu; Quan Gan; Lulu Huang; Xingyu Pan; Tongwei Liu; Ruiyang Wang; Limengjie Wang; Li Zhang; Han Li; Lixia Wang; Sining Liu; Jiao Li; et al. (CATENA, 2024)

Adaptive tracking guidance for powered aeroassisted orbital maneuver under system uncertainties and input constraints - Qijia Yao; Qing Li; Hongwei Han; Jilin Chen (Advances in Space Research, 2024)

Taxonomic and functional dynamics of nirS denitrifiers along a salinity gradient in the Pearl River Estuary - Hongwei Zhou; Hao Zhang; Xinping He; Cheng Liu; Fozia; Qian Cui; Hongjun Yang; Chunyu Zhao; Han Zhang; Huanhuan Hu; Zongxiao Zhang (Frontiers in Marine Science, 2024)
Understanding the factors that shape the diversity, distribution, and function of denitrifying microbes is vital for managing nitrogen cycling in these ecosystems. This study explores the diversity, biogeographic distribution, assembly processes, interaction, and denitrification potential of the nirS -encoding microbial community ( nirS denitrifier) in the Pearl River Estuary based on high-throughput and metagenomics sequencing dataset. The results of this study show that salinity is a crucial regulatory environmental factor that determines the spatial distribution, phylogenetic turnover, and co-occurrence patterns of nirS denitrifiers. Additionally, the dissolved organic carbon (DOC), suspended sediment concentration (SSC), and dissolved oxygen (DO) in water also significantly impact the biodiversity and abundance of nirS denitrifiers. Furthermore, our findings demonstrate that, in comparison to environmental factors, the ecological and evolutionary characteristics of nirS denitrifiers play a more prominent role in regulating their denitrification potential, suggesting that alterations in the microbial community within dynamic changes in estuarine water can profoundly affect its denitrification function. Our results indicate the significant roles of denitrification microbial structure and phylogenetic characteristics in maintaining their ecological functions. Future studies should continue to explore the interactions between microbial communities and environmental factors to further elucidate the denitrification process in estuaries and its implications for ecosystem health and water quality.

Electric field-enhanced heterogeneous catalytic ozonation (EHCO) process for sulfadiazine removal: The role of cathodic reduction - Xu Yin; Jie Zhang; Siru Chen; Wei Li; Hongwei Zhu; Kajia Wei; Yonghao Zhang; Haoming Chen; Weiqing Han (Chemosphere, 2024)

Hepatotoxic of polystyrene microplastics in aged mice: Focus on the role of gastrointestinal transformation and AMPK/FoxO pathway - Pengfei Xie; Pengcheng Li; Xiaoshan Zhu; Deshan Chen; Mohammad Mehdi Ommati; Hongwei Wang; Lei Han; Shixiao Xu; Ping Sun (Science of The Total Environment, 2024)

Analysis of key enzyme activity and aroma volatile compounds in microwave-irradiated quinoa during storage - Hongwei Cao; Jinzhe Han; Rulian Sun; Zhaoxia Li; Yu Zhang; Hongdong Song; Kai Huang; Ying Zhang; Xiao Guan (Journal of Cereal Science, 2024)

Flexural behavior of GFRP-RC beams confined with CFRP in compression zone - Hongwei Wang; Jinjin Xu; Xu Jiang; Xiaoyan Han; Kaiming Pan; Rena C. Yu; Zhimin Wu (Engineering Structures, 2024)

Evaluation of toxicity of heated tobacco products aerosol and cigarette smoke to BEAS-2B cells based on 3D biomimetic chip model - Hongjuan Wang; Fengjun Lu; Yushan Tian; Sen Zhang; Shulei Han; Yaning Fu; Jun Li; Pengxia Feng; Zhihao Shi; Huan Chen; Hongwei Hou (Toxicology in Vitro, 2024)

The CropGPT project: Call for a global, coordinated effort in precision design breeding driven by AI using biological big data - Wanchao Zhu; Rui Han; Xiaoyang Shang; Tao Zhou; Chengyong Liang; Xiaomeng Qin; Hong Chen; Zaiwen Feng; Hongwei Zhang; Xingming Fan; Weifu Li; Lin Li (Molecular Plant, 2024)

An asymmetric electrode matching reversible kinetics of oxygen reaction for a rechargeable Zn-air battery - Shuxin Li; Han Zhang; Lin Wu; Hongwei Zhao; Lin Tao; Lixiang Li; Chengguo Sun; Dongying Ju; Baigang An (Chemical Engineering Journal, 2024)

Environmental impact assessment of a combined bioprocess for hydrogen production from food waste - Xietian Zheng; Jiucai Wang; Jingang Huang; Xiaobin Xu; Junhong Tang; Pingzhi Hou; Wei Han; Hongwei Li (Waste Management, 2024)

Warming effects on C:N:P stoichiometry and nutrient limitation in terrestrial ecosystems - Hongwei Xu; Minggang Wang; Chengming You; Bo Tan; Lin Xu; Han Li; Li Zhang; Lixia Wang; Sining Liu; Guirong Hou; Yang Liu; Zhenfeng Xu; et al. (Soil and Tillage Research, 2024)

The regulatory mechanisms of delayed senescence of nitric oxide treatment of hyacinth beans - Lichun Han; Zhengrong Wang; Christopher B. Watkins; Lili Ma; Xuelian He; Chunmei Bai; Hongwei Wang; Qing Wang; Jinhua Zuo; Yanyan Zheng (Postharvest Biology and Technology, 2024)

Active disturbance rejection control strategy for PEMFC oxygen excess ratio based on adaptive internal state estimation using unscented Kalman filter - Hongwei Yue; Hongwen He; Mo Han; Sikai Gong (Fuel, 2024)

Enhanced dispersing properties of kaolin due to high-strength kneading process - Qiang Ma; Yubiao Li; Jingxuan Liu; Hongwei Ying; Hongfei Han; Xin Chen (Applied Clay Science, 2024)

Coupling effects of soil organic carbon and moisture under different land use types, seasons and slope positions in the Loess Plateau - Jianguo Zhang; Zhilong Lan; Hongwei Li; Muhammad Tauseef Jaffar; Xiong Li; Lele Cui; Jiale Han (CATENA, 2023)

Effects of PM2.5 emissions from household fuel combustion on biomarkers and pulmonary function in rural areas of Fenwei Plain, China - Rong Feng; Hongmei Xu; Hongwei Lu; Bei Han; Yue Cheng; Yunxuan Gu; Jian Sun; Liu Yang; Zhenxing Shen; Junji Cao (Atmospheric Pollution Research, 2023)

Decoding the marine biogeochemical cycling of mercury by stable mercury isotopes - Lin Yang; Ben Yu; Deming Han; Kun Zhang; Hongwei Liu; Cailing Xiao; Ligang Hu; Yongguang Yin; Jianbo Shi; Guibin Jiang (Critical Reviews in Environmental Science and Technology, 2023)

Disentangling the relative importance of precipitation, biocrust succession, and shrub cover in mediating soil phoD-harbouring communities and organic phosphorus mineralisation - Lin Xu; Xiangzhen Li; Chaonan Li; Yongping Kou; Jiabao Li; Minjie Yao; Bingchang Zhang; Lixia Wang; Hongwei Xu; Chengming You; Han Li; Sining Liu; et al. (Soil Biology and Biochemistry, 2023)

Effects of acid modified biochar on potassium uptake, leaching and balance in an alternate wetting and drying paddy ecosystem - Hongwei Han; Taotao Chen; Chang Liu; Feng Zhang; Yidi Sun; Yikui Bai; Jun Meng; Daocai Chi; Wenfu Chen (Science of The Total Environment, 2023)

Response of soil phosphorus fractions to litter removal in subalpine coniferous forest - Linhui Zhang; Ya Shen; Yifan Hu; Jihong Li; Yao Liu; Su Chen; Lixia Wang; Sining Liu; Han Li; Chengming You; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2023)

Research on the hydrodynamic performance of AUVs in small size open channel area - Jian Cao; Yaoqi Feng; Yueming Li; Hongwei Li; Chao Han; Yushan Sun; Zhaohang Liu (Ocean Engineering, 2023)

Reproducible Abnormalities and Diagnostic Generalizability of White Matter in Alzheimer’s Disease - Yida Qu; Pan Wang; Hongxiang Yao; Dawei Wang; Chengyuan Song; Hongwei Yang; Zengqiang Zhang; Pindong Chen; Xiaopeng Kang; Kai Du; Lingzhong Fan; Bo Zhou; et al. (Neuroscience Bulletin, 2023)

Corrigendum to “Maternal linuron exposure alters testicular development in male offspring rats at the whole genome level” [Toxicology 389 (2017) 13–20] - Jianwei Bai; Hua Han; Feng Wang; Liyu Su; Hongwei Ding; Xiyin Hu; Binli Hu; Hong Li; Wei Zheng; Yan Li (Toxicology, 2023)

Paleo-Asian oceanic crust trapped by irregular continental margin contributes to continental growth: Evidence from airborne gravity and magnetic imaging across the Alxa tectonic belt, Central Asia - Xingtao Kuang; Xi Xu; Hongwei Duan; Baobao Cao; Fangxin Ning; Mengchu Xiao; Song Han; Daoqing Zhou; Baodi Wang (Gondwana Research, 2023)

An extra-chelator-free fenton process assisted by electrocatalytic-induced in-situ pollutant carboxylation for target refractory organic efficient treatment in chemical-industrial wastewater - Wei Li; Kajia Wei; Xu Yin; Hongwei Zhu; Quanqi Zhu; Xiaoyuan Zhang; Siqi Liu; Weiqing Han (Environmental Research, 2023)

Quantitative detection of naphthenic acids in wastewater based on superior fluorescence performance of nitrogen-rich carbon quantum dots - Yize Liu; Meiyu Li; Ruoyao Zhang; Tengda Zhao; Jing Han; Aibin Kang; Chunmao Chen; Hongwei Ren; Erhong Duan (Science of The Total Environment, 2023)

Network prediction of surgical complication clusters: a prospective multicenter cohort study - Xiaochu Yu; Peng Wu; Zixing Wang; Wei Han; Yuguang Huang; Shijie Xin; Qiang Zhang; Shengxiu Zhao; Hong Sun; Guanghua Lei; Taiping Zhang; Luwen Zhang; et al. (Science China Life Sciences, 2023)

Near-infrared carbon quantum dots from PEG-based deep eutectic solvents for high-accuracy quantitative analysis of naphthenic acids in wastewater - Hongwei Ren; Yize Liu; Ruoyao Zhang; Yi Zheng; Tengda Zhao; Jing Han; Chunmao Chen; Erhong Duan (Journal of Environmental Chemical Engineering, 2023)

Excessive ER-phagy contributes to ochratoxin A-induced apoptosis - Huiqiong Deng; Wenying Chen; Boyang Zhang; Yiwen Zhang; Lingyun Han; Qipeng Zhang; Song Yao; Hongwei Wang; Xiao Li Shen (Food and Chemical Toxicology, 2023)

Iron oxides act as an alternative electron acceptor for aerobic methanotrophs in anoxic lake sediments - Biao Li; Ye Tao; Zhendu Mao; Qiujin Gu; Yixuan Han; Baolan Hu; Hongwei Wang; Anxing Lai; Peng Xing; Qinglong L Wu (Water Research, 2023)

Inhibiting N2O emissions and improving environmental benefits by integrating garlic growing in grain production systems - Dan Liu; Hongwei Dong; Chi Ma; Qin Mo; Bo Liu; Ahmad Irshad; Hui Li; Baoping Yang; RuiXia Ding; Altyn Shayakhmetoya; Xudong Zhang; Qingfang Han (Agriculture, Ecosystems & Environment, 2023)

Investigation of the CO2 capture behavior in multiple-site natural deep eutectic solvents - Hongwei Ren; Yize Liu; Ruoyao Zhang; Tengda Zhao; Jing Han; Zhiyang Zheng; Erhong Duan (Process Safety and Environmental Protection, 2023)

Indoor air particles in research vessel from Shanghai to Antarctic: Characteristics, influencing factors, and potential controlling pathway - Xudong Wu; Fange Yue; Jiancheng Wang; Xiawei Yu; Hongwei Liu; Weihua Gu; Mingming Han; Juan Li; Zhouqing Xie (Journal of Environmental Sciences, 2023)

Retraction Note: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2023)

Electrochemical oxidation of bio-treated landfill leachate using a novel dynamic reactive electrochemical membrane (DREM) - Xu Yin; Wei Li; Hongwei Zhu; Jie Zhang; Liankai Gu; Kajia Wei; Zhanping Gao; Laisong Zhu; Weiqing Han (Journal of Hazardous Materials, 2023)

An aging giant at the center of global warming: Population dynamics and its effect on CO2 emissions in China - Hongwei Guo; Jia Jiang; Yuanyuan Li; Xinxin Long; Ji Han (Journal of Environmental Management, 2023)

Are olefin aromatization reactions structure sensitive over Al pairs and single Al in H-ZSM-5 Zeolite? - Mengjiao Xing; Yunlei Chen; Jian Cao; Yuanlong Han; Zhichao Tao; Fei Wang; Kun Hao; Ling Zhang; Wentao Zheng; Hongwei Xiang; Yong Yang; Yongwang Li; et al. (Fuel, 2023)

Lonp1 and Sig-1R contribute to the counteraction of ursolic acid against ochratoxin A-induced mitochondrial apoptosis - Qipeng Zhang; Wenying Chen; Boyang Zhang; Yiwen Zhang; Yuqing Xiao; Yichen An; Lingyun Han; Huiqiong Deng; Song Yao; Hongwei Wang; Xiao Li Shen (Food and Chemical Toxicology, 2023)

Molecular mechanisms of interrod spacing-mediated osseointegration via modulating inflammatory response and osteogenic differentiation - Meng Yu; Hongwei Yang; Bo Li; Rong Wang; Yong Han (Chemical Engineering Journal, 2023)

Multifunctional PVCL nanogels enable magnetic resonance imaging and immunostimulated radiotherapy of orthotopic glioblastoma - Meijuan He; Tingting Xiao; Yihui Wang; Hongwei Yu; Zilin Wang; Xiangyang Shi; Han Wang (Chemical Engineering Journal, 2023)

Integrated electro-Fenton system based on embedded U-tube GDE for efficient degradation of ibuprofen - Kaiqiang Shi; Yi Wang; Anlin Xu; Hongwei Zhu; Liankai Gu; Xiaodong Liu; Jinyou Shen; Weiqing Han; Kajia Wei (Chemosphere, 2023)

Visible light-triggered smart photoreversible color switching systems based on VOx QDs for constructing smart corrosion resistant coatings on AA2024-T3 - Sharjeel Ahmed; Hongwei Shi; Ningjie Gao; Fuchun Liu; Izuchukwu K. Nwokolo; Jiwen Li; Wanyu Zhang; Mustehsin Ali; Imran Ali; En-Hou Han (Chemical Engineering Journal, 2023)

Cellular Heterogeneity and Plasticity of Skin Epithelial Cells in Wound Healing and Tumorigenesis - Jingru Wang; Jia He; Meishu Zhu; Yan Han; Ronghua Yang; Hongwei Liu; Xuejuan Xu; Xiaodong Chen (Stem Cell Reviews and Reports, 2022)
Cellular differentiation, the fundamental hallmark of cells, plays a critical role in homeostasis. And stem cells not only regulate the process where embryonic stem cells develop into a complete organism, but also replace ageing or damaged cells by proliferation, differentiation and migration. In characterizing distinct subpopulations of skin epithelial cells, stem cells show large heterogeneity and plasticity for homeostasis, wound healing and tumorigenesis. Epithelial stem cells and committed progenitors replenish each other or by themselves owing to the remarkable plasticity and heterogeneity of epidermal cells under certain circumstance. The development of new assay methods, including single-cell RNA sequence, lineage tracing assay, intravital microscopy systems and photon-ablation assay, highlight the plasticity of epidermal stem cells in response to injure and tumorigenesis. However, the critical mechanisms and key factors that regulate cellular plasticity still need for further exploration. In this review, we discuss the recent insights about the heterogeneity and plasticity of epithelial stem cells in homeostasis, wound healing and skin tumorigenesis. Understanding how stem cells collaborate together to repair injury and initiate tumor will offer new solutions for relevant diseases. Graphical Abstract Schematic abstract of cellular heterogeneity and plasticity of skin epithelial cells in wound healing and tumorigenesis

Fine mapping of QFlw-5B, a major QTL for flag leaf width in common wheat (Triticum aestivum L.) - Chunhua Zhao; Xijian Liu; Hongwei Liu; Wenchao Kong; Zhuochao Zhao; Shengren Zhang; Saining Wang; Yingzi Chen; Yongzhen Wu; Han Sun; Ran Qin; Fa Cui (Theoretical and Applied Genetics, 2022)

Establishment of a set of wheat-rye addition lines with resistance to stem rust - Chang Liu; Jing Wang; Shulan Fu; Long Wang; Hongwei Li; Mian Wang; Yuhong Huang; Qinghua Shi; Yonghong Zhou; Xianrui Guo; Congle Zhu; Jing Zhang; et al. (Theoretical and Applied Genetics, 2022)

Combined overexpression of four transcription factors promotes effector T cell dedifferentiation toward early phenotypes - Lijun Yan; Yusheng Ou; Shengfang Xia; Jianqing Huang; Wenfeng Zhang; Hongwei Shao; Han Shen; Huaben Bo; Changli Tao; Jinquan Wang; Fenglin Wu (Immunogenetics, 2022)

Spatial–temporal evolution pattern and prediction analysis of flood disasters in China in recent 500 years - Cuixia Wei; Bing Guo; Hailing Zhang; Baomin Han; Xiangshen Li; Huihui Zhao; Yuefeng Lu; Chao Meng; Xiangzhi Huang; Wenqian Zang; Hongwei Wu (Earth Science Informatics, 2022)

Correction to: What are the dominant influencing factors on the soil erosion evolution process in the Yellow River Basin? - Hongwei Wu; Bing Guo; Haorun Xue; Wenqian Zang; Baomin Han; Fei Yang; Yuefeng Lu; Cuixia Wei (Earth Science Informatics, 2021)

What are the dominant influencing factors on the soil erosion evolution process in the Yellow River Basin? - Hongwei Wu; Bing Guo; Haorun Xue; Wenqian Zang; Baomin Han; Fei Yang; Yuefeng Lu; Cuixia Wei (Earth Science Informatics, 2021)

Identification and Evolutionary Analysis of FAD2 Gene Family in Green Plants - Shijiang Cao; Jiashuo Zhang; Han Cheng; Mohammad Aslam; Hongwei Lv; Wei Dong; Anqi Hu; Mingliang Guo; Qing Liu; Yuan Qin (Tropical Plant Biology, 2021)

Mapping of a major QTL for salinity tolerance at the bud burst stage in rice (Oryza sativa L) using a high-density genetic map - Lei Lei; Zhenghong Han; Bowen Cui; Luomiao Yang; Hualong Liu; Jingguo Wang; Hongwei Zhao; Wei Xin; Xianwei Li; Jiaming Li; Jingnan Cui; Shanbin Xu; et al. (Euphytica, 2021)

The prevalence and risks of major comorbidities among inpatients with pulmonary tuberculosis in China from a gender and age perspective: a large-scale multicenter observational study - Wanli Kang; Jian Du; Song Yang; Jiajia Yu; Hongyan Chen; Jianxiong Liu; Jinshan Ma; Mingwu Li; Jingmin Qin; Wei Shu; Peilan Zong; Yi Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

A wave propagation model with the Biot and the fractional viscoelastic mechanisms - Jiaming Yang; Dinghui Yang; Hongwei Han; Lingyun Qiu; Yuanfeng Cheng (Science China Earth Sciences, 2021)

Genome-Wide Analysis of the Cryptochrome Gene Family in Plants - Shijiang Cao; Sijia He; Hongwei Lv; Jiashuo Zhang; Mohammad Aslam; Han Cheng; Anqi Hu; Guangqiu Cao; Xingtan Zhang; Yuan Yu; Yuan Qin (Tropical Plant Biology, 2020)

RETRACTED ARTICLE: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2020)

Naked oats biochar-supported nanoscale zero-valent iron composite: effects on Cd immobilization and enzyme activities in Ulansuhai River sediments of China - Baohong Han; Lei Song; Hao Li; Hongwei Song (Journal of Soils and Sediments, 2019)

Identification and validation of major QTLs and epistatic interactions for seed oil content in soybeans under multiple environments based on a high-density map - Qi Zhaoming; Zhang Xiaoying; Qi Huidong; Xin Dawei; Han Xue; Jiang Hongwei; Yin Zhengong; Zhang Zhanguo; Zhang Jinzhu; Zhu Rongsheng; Hu Zhenbang; Liu Chunyan; et al. (Euphytica, 2017)

Speciation analysis of arsenic compounds in seafood by ion chromatography-atomic fluorescence spectrometry - Tingting Han; Hongwei Ji; Huixin Li; He Cui; Tian Song; Xiaojuan Duan; Qianlin Zhu; Feng Cai; Li Zhang (Journal of Ocean University of China, 2017)

DDX50 inhibits the replication of dengue virus 2 by upregulating IFN-β production - Peijun Han; Wei Ye; Xin Lv; Hongwei Ma; Daihui Weng; Yangchao Dong; Linfeng Cheng; Hesong Chen; Liang Zhang; Zhikai Xu; Yingfeng Lei; Fanglin Zhang (Archives of Virology, 2017)

Correlation between status of epidermal growth factor receptor mutation and distant metastases of lung adenocarcinoma upon initial diagnosis based on 1063 patients in China - Hongwei Li; Jianzhong Cao; Xiaqin Zhang; Xing Song; Weili Wang; Sufang Jia; Zhengran Li; Haixia Jia; Xing Cao; Wei Zhou; Jianhong Lian; Songye Han; et al. (Clinical & Experimental Metastasis, 2017)

Global mapping of artificial surfaces at 30-m resolution - XueHong Chen; Xin Cao; AnPing Liao; LiJun Chen; Shu Peng; Miao Lu; Jin Chen; WeiWei Zhang; HongWei Zhang; Gang Han; Hao Wu; Ran Li (Science China Earth Sciences, 2016)

Influence of Large Syncline on In Situ Stress Field: A Case Study of the Kaiping Coalfield, China - Jun Han; Hongwei Zhang; Bin Liang; Hai Rong; Tianwei Lan; Yuanzheng Liu; Ting Ren (Rock Mechanics and Rock Engineering, 2016)

Combined mutagenesis of Rhodosporidium toruloides for improved production of carotenoids and lipids - Chaolei Zhang; Hongwei Shen; Xibin Zhang; Xue Yu; Han Wang; Shan Xiao; Jihui Wang; Zongbao K. Zhao (Biotechnology Letters, 2016)

Fine Mapping of qDor7, a Major QTL Affecting Seed Dormancy in Sorghum (Sorghum bicolor (L.) Moench) - Pan Li; Emma S. Mace; Yan Guo; Lijie Han; Mumu Wang; Yanfang He; Jun Chen; Nana Yuyama; David R. Jordan; Hongwei Cai (Tropical Plant Biology, 2016)

Influence of mechanical damage generated by small space debris on electrostatic discharge - MingHui Cai; HongWei Li; JianWei Han (Science China Earth Sciences, 2016)

Introduction of parameterized sea ice drag coefficients into ice free-drift modeling - Peng Lu; Zhijun Li; Hongwei Han (Acta Oceanologica Sinica, 2016)

High-density mapping of the major FHB resistance gene Fhb7 derived from Thinopyrum ponticum and its pyramiding with Fhb1 by marker-assisted selection - Jun Guo; Xiuli Zhang; Yanlin Hou; Jinjin Cai; Xiaorong Shen; Tingting Zhou; Huihui Xu; Herbert W. Ohm; Hongwei Wang; Anfei Li; Fangpu Han; Honggang Wang; et al. (Theoretical and Applied Genetics, 2015)

Fine mapping of qGW1, a major QTL for grain weight in sorghum - Lijie Han; Jun Chen; Emma S. Mace; Yishan Liu; Mengjiao Zhu; Nana Yuyama; David R. Jordan; Hongwei Cai (Theoretical and Applied Genetics, 2015)

An assessment of arctic sea ice concentration retrieval based on “HY-2” scanning radiometer data using field observations during CHINARE-2012 and other satellite instruments - Lijiang Shi; Peng Lu; Bin Cheng; Juha Karvonen; Qimao Wang; Zhijun Li; Hongwei Han (Acta Oceanologica Sinica, 2015)

The uniaxial compressive strength of the Arctic summer sea ice - Hongwei Han; Zhijun Li; Wenfeng Huang; Peng Lu; Ruibo Lei (Acta Oceanologica Sinica, 2015)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

The Novel Tetramethylpyrazine Bis-nitrone (TN-2) Protects Against MPTP/MPP+-Induced Neurotoxicity via Inhibition of Mitochondrial-Dependent Apoptosis - Daping Xu; Hongwei Duan; Zaijun Zhang; Wei Cui; Liang Wang; Yewei Sun; Ming Lang; Pui Man Hoi; Yifan Han; Yuqiang Wang; Simon MingYuen Lee (Journal of Neuroimmune Pharmacology, 2014)

Study on the Effect of Kidney Transplantation on the Health of the Patients’ Offspring: A Report on 252 Chinese Children - Longgen Xu; Peng Han; Yong Liu; Hongwei Wang; Yirong Yang; Feng Qiu; Wanling Peng; Ligong Tang; Jing Fu; Xiaofeng Zhu; Youhua Zhu (Cell Biochemistry and Biophysics, 2014)

Erratum to: Identification of QTLs for seed and pod traits in soybean and analysis for additive effects and epistatic effects of QTLs among multiple environments - Zhe Yang; Dawei Xin; Chunyan Liu; Hongwei Jiang; Xue Han; Yanan Sun; Zhaoming Qi; Guohua Hu; Qingshan Chen (Molecular Genetics and Genomics, 2013)

Identification of QTLs for seed and pod traits in soybean and analysis for additive effects and epistatic effects of QTLs among multiple environments - Zhe Yang; Dawei Xin; Chunyan Liu; Hongwei Jiang; Xue Han; Yanan Sun; Zhaoming Qi; Guohua Hu; Qingshan Chen (Molecular Genetics and Genomics, 2013)

Knockdown BMI1 expression inhibits proliferation and invasion in human bladder cancer T24 cells - Wu Liang; Dingjun Zhu; Xuejiang Cui; Jiarui Su; Hongwei Liu; Jinli Han; Fengjin Zhao; Wenlian Xie (Molecular and Cellular Biochemistry, 2013)

Effects of SLCO1B1 polymorphisms on the pharmacokinetics and pharmacodynamics of repaglinide in healthy Chinese volunteers - Jiake He; Zhixia Qiu; Ning Li; Yang Yu; Yang Lu; Deen Han; Tingting Li; Di Zhao; Wei Sun; Fang Fang; Jianheng Zheng; Hongwei Fan; et al. (European Journal of Clinical Pharmacology, 2011)

TCR mispairing in genetically modified T cells was detected by fluorescence resonance energy transfer - Hongwei Shao; Wenfeng Zhang; Qinglian Hu; Fenglin Wu; Han Shen; Shulin Huang (Molecular Biology Reports, 2010)

Construction of a high-density SSR marker-based linkage map of zoysiagrass (Zoysia japonica Steud.) - Manli Li; Nana Yuyama; Mariko Hirata; Jianguo Han; Yunwen Wang; Hongwei Cai (Euphytica, 2009)

Carrying capacity of marine region in Liaoning Province - Qianbin Di; Zenglin Han; Guichun Liu; Hongwei Chang (Chinese Geographical Science, 2007)

Inhibitory effects of compounds isolated from fruit of Juglans mandshurica on pancreatic lipase - Likun Han; Wei Li; Sanae Narimatsu; Lijuan Liu; Hongwei Fu; Hiromichi Okuda; Kazuo Koike (Journal of Natural Medicines, 2007)